INOVASI PEMANFAATAN APLIKASI RENCANA KERJA, ANGGARAN, MONITORING, DAN EVALUASI (RAVASA) DI UNIVERSITAS NEGERI SURABAYA: Studi Pada Kantor Direktorat Perencanaan, Pengembangan, dan Pelaporan Universitas Negeri Surabaya - mario ananto; Meirinawati; Tjitjik Rahaju; Indah Prabawati (Publika, 2026)
Universitas Negeri Surabaya (UNESA), as a State University with Legal Entity status (PTNBH), is required to implement transparent, accountable, and performance-based governance in planning and budgeting. The growing complexity of institutional management necessitates innovation through integrated information systems, including the Work Plan, Budget, Monitoring, and Evaluation Application (RAVASA). This study aims to analyse the innovation in the utilization of RAVASA in supporting institutional performance and governance at UNESA. A descriptive qualitative approach with a case study method was employed at the Directorate of Planning, Development, and Reporting. Data were collected through interviews, observations, and documentation, and analysed using the Miles and Huberman model within the framework of Rogers’ Diffusion of Innovation theory. The findings indicate that RAVASA provides a relative advantage by integrating planning, budgeting, monitoring, and evaluation processes, thereby improving efficiency, transparency, and accountability in financial management. The system is compatible with organizational needs and PTNBH regulations, although system complexity remains a challenge for some users. This study recommends strengthening human resource capacity and continuous system refinement to optimize the sustainable use of RAVASA.